INTEGRATED GEOELECTRICAL AND PUMPING TEST ASSESSMENT OF AQUIFER CHARACTERISTIC IN METROPOLITAN KANO, NORTHWESTERN NIGERIA - Sani, Yakubu Khalifa; Aliyu, Mohammed (FUDMA Journal of Sciences, 2026)
Groundwater is the major source of water supply in arid and semi-arid regions around the world. However, the depletion of groundwater resources has become a serious issue in many places due to excessive extraction combined with climate change impacts. This study aims to evaluate the current state of groundwater depletion and its socioeconomic consequences in Kano metropolitan. The research combines data analysis of groundwater levels using previous pump test data, the integration of Geophysical investigation employing vertical electrical sounding (VES) and GIS approaches to analyze the groundwater level using the widely accepted MODFLOW-2005 model. The results show that groundwater levels have declined steadily over the past few decades due to increasing water demand from the growing population, agricultural expansion, and industrial development. The resistivity method used in has greatly assisted in delineating subsurface. The interpreted results of the thirty-seven (37) points were showing three to five subsurface layers which include topsoil, lateral soil, weathered rock, fractured basement and fresh basement varied from 3.515 to 10297-ohm m, 10.99 to 1508.5-ohm m, 0.919 to 953.95-ohm m, 2.086 to 15190-ohm m and 0.0106 to 42304-ohm m respectively. Dar-Zarrouk parameters such as longitudinal conductance (S) and transverse resistance (R) values varied from 0.000426 to 6.168041 Ω–1 and 25.57056 to 125809.6 Ωm2 respectively. GIS complements these methods by enabling the visualization and spatial analysis of groundwater-related data. Through the integration of aquifer characteristic and geophysical data.
Keywords: Groundwater; Depletion; Resistivity; Pump; Aquifer